International Legal Custom аs an Object of Interpretation: Modern Approaches and Discussions - Карвацька, Світлана Богданівна (International Journal of Humanities and Applied Social Science, 2021)
The article determines that the transition from a liberal state system to a welfare state system has adapted the concept of international legal custom and the correlation between its two elements. With the emergence of new members of the international system, a new environment has emerged where there is no clear common understanding of the definition and content of international law rules. The lack of an effective, consistent method of identifying international custom dictates the requirement to seek an effective methodology for interpreting international legal customs actively. The article finds out that often competing interpretations arise about the same practice. Therefore, it is necessary to find the interpretation offering more tools for practice, with other things being equal. If a deductive methodology seeks a connection between principle and law, an inductive one looks for social facts that support common practice. It is proved that a qualitatively new constructive interpretation has the potential to provide a better interpretation of international community practice. In conclusion, it is stated that the result of constructive interpretation should be the orientation of the goal into practice.
Keywords: customary international law, “practice”, “opinio juris”, constructive interpretation, methodology for interpreting.